Soméah Culture as a Shaper of Brand Personality in Sundanese Ethnic Society: Implications of Personal Branding and Cultural Transactions - Ratnasari, Dewi; Sidiq, Fahmi; Kalfin (International Journal of Humanities, Law, and Politics, 2023)
This research reviews the role of soméah culture in shaping the brand personality of the Sundanese people. Someméah reflects values such as friendliness, politeness, and openness which are reflected in daily communication behavior. The results showed that soméah culture influenced communication behavior, including the use of words such as "punten" and "mango." Apart from that, soméah culture also influences other aspects, such as a friendly physical appearance and a high sense of humor. Soméah culture plays an important role in building positive cultural relations, especially in interactions with non-Sundanese communities. This research also illustrates how soméah culture can be maintained and inherited and identifies the implications of personal branding and cultural transactions in preserving local culture.